Pengaruh Playstation Terhadap Prestasi Belajar Siswa Bidang Studi Aqidah Akhlak Kelas IV Di Madrasah Ibtidaiyah Muhammadiyah 03 Weru - Ana Saifatul Khusnah; Bahrus Surur; Subhan Adi Santoso (jurnal Mahasiswa Pencerah, 2020)
In this study the author uses quantitative methods, while for data collection using questionnaires, documentation, observation, while the population is the entire number of fourth grade students at MI Muhammdiyah 03 Weru-Paciran, totaling 35 students and 25 being taken as samples. To analyze the final results the author uses the Product Moment formula with the formula: rxy= (?xy)/?((?x^2 )(?y²)).In this study, the results obtained from data analysis using the Product Moment formula which the results reached 1.0208 were rounded up to 1. So the results and conclusions can be obtained that playing Playstation games is very influential on student achievement in the Aqidah Akhlak class IV study at MI Muhammdiyah 03 Weru-Paciran.